Strategi Pemasaran dalam Meningkatkan Omzet Penjualan Kopi Baradjawa pada Kedai Kopi dengan Konsep Budaya Jawa - Baharudinsyah, Mohammad Vavian; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research has the main objective of knowing and analyzing marketing strategies to increase sales turnover at Baradjawa Coffee, which is a coffee shop in Surabaya with the concept of Javanese culture. The research conducted was descriptive qualitative research. This research was conducted at Baradjawa Coffee. The subjects of this research are owners, employees, and consumers. The data analysis method used in this research is SWOT analysis using the IFAS and EFAS tables. The results of the research analysis using IFAS and EFAS, Baradjawa Coffee has strength factors received a total score of 3.23 while the weakness factor received a total score of 0.36. Threats receive a total score of 1.37 while opportunities receive a total score of 1.94. Overall, the total value of internal strategy factors is 3.59 while the total value of external strategy factors is 3.31. Judging from the consequences of the SWOT line, Baradjawa Coffee is in quadrant I with a value of (X;Y) (2.87; 0.57), namely by using aggressive planning. Making plans that require strengths to become opportunities is an aggressive strategy.